Application of oxygen vector to aspergillus flavus cultivation - Nasimjan, Binti Abd Kahar (Universiti Malaysia Sarawak (UNIMAS), 2013)
The influence of different types of oxygen vectors (silicone oil, paraffin and Il-dodecane) on kojic acid production by Aspergillus jlavlls NSH9 in shaking-flask cultivations was investigated. Introduction of silicone oil in the cultivation gave the maximum kojic acid production of 0.256 giL which was 1.15 to 1.58 fold higher than that yielded by paraffin and ndodecane. From this study, the presence of oxygen vectors were able to increase biomass and koj ic acid production by 1.21 to 2.61 fold and 1.85 to 2.94 fold respectively compared to fermentation without the oxygen vector. Addition of silicone oil at 6% (v/v) exhibited the highest peak of kojic acid production (1.465 giL) compared to other concentrations 1-5% (v/v) tested. The results from the present works indicate the positive roles of oxygen carrier compound particularly silicone oil in enhancing the cultivation of A. jlavus NSH9 and consequently the productivity of kojic acid fermentation.